STUDIES ON THE PROPAGATION IN VITRO OF POLIOMYELITIS VIRUSES : IV. VIRAL MULTIPLICATION IN A STABLE STRAIN OF HUMAN MALIGNANT EPITHELIAL CELLS (STRAIN HELA) DERIVED FROM AN EPIDERMOID CARCINOMA OF THE CERVIX - Scherer, William F. (The Rockefeller University Press, 1953)
The cells of a human epithelial cancer cultivated en masse have been shown to support the multiplication of all three types of poliomyelitis virus. These cells (strain HeLa of Gey) have been maintained in vitro since their derivation from an epidermoid carcinoma of the cervix in February, 1951. As the virus multiplied it caused in from 12 to 96 hours degeneration and destruction of the cancer cells. The specific destructive effect of the virus was prevented by adding homotypic antibody to the cultures but not by adding heterotypic antibodies. Methods for the preparation of large numbers of replicate cultures with suspensions of strain HeLa cells were described. The cells in suspension were readily quantitated by direct counts in a hemocytometer. A synthetic solution that maintains cellular viability was employed for viral propagation. The experimental results demonstrate the usefulness of strain HeLa cells for (a) the quantitation of poliomyelitis virus, (b) the measurement of poliomyelitis antibodies, and (c) the production of virus.